Innovative Strategy to address Sexualities and Eroticism: Art Galleries with University Students (Docentes 2.0 Journal, 2024)
The approach to human sexuality is controversial, as stated in previous research that sought to address some themes of sexuality, art, and education. The present study explored the potential of art and artistic expressions as an innovative methodological strategy to address sexuality and eroticism in university settings. The research was based on the action research method, adopting a humanistic paradigm with a qualitative approach, narrative design, interpretive type, and longitudinal section. Participants were students from University 1 and University 2, actively involved in seven intervention versions. Data collection techniques included field diaries and semi-structured interviews. Each intervention version presented distinctive characteristics, generating great proposals and learning for participants and gallery visitors. Various reactions, attitudes, and behaviors were observed and documented through interviews and observation records. The intervention reached 50 students and a population of 1,750 people, including the virtual version. The study demonstrated the effectiveness of art and artistic expressions as an innovative methodological strategy to address sexuality and eroticism in university environments. This strategy promotes social interaction, motivation for artistic creation, and sexual education in a creative and accessible way.
Keywords: Sexuality; innovative strategy; eroticism; learning; gallery